(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article analyzes various management decision-making processes in the hotel industry for hotel managers at various levels under conditions of insufficient or unreliable information, and examines decision-making mechanisms using various mathematical criteria. Flexible algorithms for making management decisions are proposed.